Corpus callosum morphology in first-episode and chronic schizophrenia: combined magnetic resonance and diffusion tensor imaging study of Chinese Singaporean patients. (January 2014) - Collinson, Simon L.; Gan, Swu Chyi; Woon, Puay San; Kuswanto, Carissa; Sum, Min Yi; Yang, Guo Liang; Lui, Ji Min; Sitoh, Yih Yian; Nowinski, Wieslaw L.; Sim, Kang
Abstract : Background: Abnormalities in the corpus callosum have been reported in patients with schizophrenia for over 30 years but the influence of inter-individual differences and illness characteristics remains to be fully elucidated. Aims: To examine the influence of individual and illness characteristics on the corpus callosum in Chinese Singaporean patients with schizophrenia. Method: Using magnetic resonance and diffusion tensor imaging, mean corpus callosum area, volume and fractional anisotropy were investigated in 120 Chinese Singaporean patients (52 with chronic and 68 with first-episode schizophrenia) and compared with data from 75 matched healthy controls. Results: Both area and volume were significantly reduced in patients relative to controls but no significant differences in corpus callosum existed between genders in either patients or controls. Differences in area and volume of the corpus callosum were greatest in patients whose condition was chronic relative to patients with a first episode and controls. Anterior callosum in patients, regardless of chronicity, was no different to that of controls. Conclusions: Morphological abnormalities in the corpus callosum may increase with illness progression.